Explorations of the semantic learning machine neuroevolution algorithm: dynamic training data use and ensemble construction methods - Seca, Marta Sofia Lopes (2020)
Dissertation presented as the partial requirement for obtaining a Master’s degree in Data Science and Advanced Analytics